We are the very model of a moderate Muslim state: The Amman Messages and Jordan's foreign policy. (June 2016) - Gutkowski, Stacey
Despite its significance to one of the most problematic discursive binaries of the 'War on Terror', moderation has been a largely taken for granted theoretical and empirical category in the discipline of International Relations. To prompt further conversation, this article examines 'Islamic moderation' as part of Middle Eastern states' nation branding in the decade and half since 9/11, using Jordan as a case study. I argue that while Jordan's official and state-endorsed civil society efforts to promote 'moderate Islam' and interfaith dialogue stem in part from authentic interest in promoting dialogue and peace, the Jordanian Hashemite regime has also used the Amman Messages to deepen political trust with the United States, attempting to instrumentalize the moral authority of religion as a form of state productive power. It has done so by playing on a myth of religious moderation which has resonated in both the Middle East and the West since 9/11.